Simulation of memristor switching time series in response to spike-like signal. (January 2021) - Zhevnenko, D.; Meshchaninov, F.; Kozhevnikov, V.; Shamin, E.; Belov, A.; Gerasimova, S.; Guseinov, D.; Mikhaylov, A.; Gornev, E.
Abstract: Memristor based device development is among the most promising and fast developing branches of modern microelectronics. Therefore, memristor modeling remains an important task due to constant improvement in understanding of resistive switching mechanism. We present a compact model with the features of modified mobility included as well as a method of switching series approximation. In addition, the method was applied to an experimental set of switching cycles of the ZrO2 (Y)-based device. The obtained results include the extraction of model parameters for each I-V curve, the result of statistical processing of the parameters cycle-to-cycle variations, the estimation of the dynamic attractors, analysis of the region of the state variable of the model, and estimation of switching power consumption.